2010
DOI: 10.1111/j.1600-0609.2010.01478.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of occult cerebrospinal fluid involvement assessed by flow cytometry in non‐Hodgkin’s lymphoma patients at high risk of central nervous system disease in the rituximab era

Abstract: The presence of occult CNS involvement at diagnosis in patients with NHL at high risk of CNS disease is associated with a higher probability of CNS relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 36 publications
(57 reference statements)
5
42
0
5
Order By: Relevance
“…These results are consistent with several reports on the outcome of FCM+ CSF involvement in pooled analyses of aggressive B-cell lymphomas. 4,25,26 One small retrospective study showed an association between occult CSF involvement and risk of CNS relapse, and a second prospective study showed an adverse association between FCM + CSF and survival and risk of CNS progression. 25,26 The benefit of intrathecal therapy is controversial in DLBCL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with several reports on the outcome of FCM+ CSF involvement in pooled analyses of aggressive B-cell lymphomas. 4,25,26 One small retrospective study showed an association between occult CSF involvement and risk of CNS relapse, and a second prospective study showed an adverse association between FCM + CSF and survival and risk of CNS progression. 25,26 The benefit of intrathecal therapy is controversial in DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…4,25,26 One small retrospective study showed an association between occult CSF involvement and risk of CNS relapse, and a second prospective study showed an adverse association between FCM + CSF and survival and risk of CNS progression. 25,26 The benefit of intrathecal therapy is controversial in DLBCL. 9,13,24,27 The reasons for this controversy are multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…10,42,45,46 Early studies analyzing non-stabilized CSF samples by ≤4-color FCM already demonstrated increased sensitivity in between 3% and 20% of cases as compared with cytology (Table 2). 42,[47][48][49][50] More recent analyses of larger series of CSF-stabilized samples using 4-8 color FCM have confirmed the greater sensitivity of FCM vs. CC with a median proportion of occult CNSL (FCM+/CC-CSF) of 12% (range: 5%-13%) ( Table 1).…”
Section: Multiparameter Flow Cytometry Analysis Of Csf Samplesmentioning
confidence: 99%
“…Several studies comparing flow cytometry and conventional cytomorphology to detect CSF involvement in hematological malignancies (Table 2) describe samples in which flow cytometry is positive whilst cytology is negative (6,14,43,51). Presence of neurological symptoms compatible with leptomeningeal disease is highly suggestive for CNS involvement in such patients, whereas absence of symptoms and lack of recurrence of CNS disease during clinical follow-up indicate a falsepositive flow cytometric result (6,14).…”
Section: Sensitivity and Specificitymentioning
confidence: 99%
“…Results of clinical follow-up were documented in three studies. Sancho et al (51) found that a flow cytometry-positive, cytology-negative result was associated with a higher probability of CNS relapse in aggressive B-cell lymphomas, as compared to samples with absence of neoplastic cells by both methods, whereas Hegde et al (43) observed that 5/11 patients with a flow cytometry-positive, cytology-negative result relapsed in the clinical CNS and died despite having received active treatment. In addition, Bromberg et al (6) described the absence of CNS recurrence in only 1/24 flow cytometry-positive, cytology-negative patients.…”
Section: Sensitivity and Specificitymentioning
confidence: 99%